2023
DOI: 10.1590/1519-6984.247840
|View full text |Cite
|
Sign up to set email alerts
|

Second world record for two Calvatia species (Agaricaceae: Basidiomycota)

Abstract: Calvatia is a genus of gasteroid fungi, comprising about 47 species worldwide. In this paper we report the second worldwide occurrence of two poorly known species of Calvatia, recorded in the Cerrado biome of Brazil: C. oblongispora and C. nodulata. Detailed morphological descriptions and illustrations, including scanning electron micrographs of hyphae and basidiospores are provided, as well a discussion on their taxonomy and geographic distribution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…Although the REC-UEG suffers a strong environmental impact due to its location, it is still possible to observe expressive biodiversity that resists. Besides the richness of corticioid and poroid fungi that we reported, previous studies in the area also presented new occurrences for the Cerrado (Alvarenga & Xavier-Santos 2017, Camilo-Cotrim et al 2020, Ferreira-Sá et al 2023. Thus, the number of specimens collected over the years, as well as the species richness shows the importance of preservation for regional Funga representativeness.…”
Section: Discussionsupporting
confidence: 70%
“…Although the REC-UEG suffers a strong environmental impact due to its location, it is still possible to observe expressive biodiversity that resists. Besides the richness of corticioid and poroid fungi that we reported, previous studies in the area also presented new occurrences for the Cerrado (Alvarenga & Xavier-Santos 2017, Camilo-Cotrim et al 2020, Ferreira-Sá et al 2023. Thus, the number of specimens collected over the years, as well as the species richness shows the importance of preservation for regional Funga representativeness.…”
Section: Discussionsupporting
confidence: 70%
“…A portion of the basidiomycetes corresponds to gasteroid fungi, widely distributed in the tropics (Mueller et al, 2007), mainly in Brazil, where the diversity of the group increases every year (Accioly et al, 2019;Assis et al, 2022;Ferreira-Sá et al, 2021;Freitas et al, 2023;Santana & Couceiro, 2023). Studies with this group revealed the production of important substances with proven biological activity (Liu & Zhang, 2004;Dore et al, 2007;Coetze and Van Wyk, 2009), but there is a study gap regarding the discoloration of synthetic dyes.…”
Section: Trypan Blue Dye Discoloration In Solid Culture Mediummentioning
confidence: 99%